Centrifuge shaking table tests on a single pile embedded in clay subjected to earthquake excitation. Issue 2 (April 2013) - Banerjee, Subhadeep; Lee, Fook Hou
Abstract : Pile foundations are extensively used to achieve the bearing capacity required to support heavy superstructure loading, especially under adverse soil conditions. In view of this, the behavior of pile foundations under earthquake loading is an important factor affecting the integrity of infrastructures. In this paper, the results from a series of dynamic centrifuge model tests carried out at the National University of Singapore are presented. The centrifuge experiments were performed to examine response of a single pile in soft clays subjected to earthquake, with special focus on the effect of superstructure loading on the seismic soil–pile interaction. The experimental observations were then compared with the results obtained from a simple theoretical analysis, based on lumped mass approach. The centrifuge test results suggest that the pile does not move in tandem with the ground. The results also indicate that the degree of soil–pile interaction depends on the presence of the superstructural load on the top of the pile.